Modeling of elastic slab with periodic breaks (Archives of Mechanics - Test, 2001)
An elastic slab having periodic breaks across its cross-section is loaded by space-harmonic forces applied to its surfaces. Due to the breaks, the slab displacement response to the load includes a series of space-harmonics. A method is proposed for evaluation of the slab harmonic response within a presumed spectral domain.